Laboratory safety for chemistry students - Hill, Robert H. , 1945-; Finster, David C. , 1953- (Wiley, 2010)
Laboratory Safety provides the knowledge and models of good practice needed by students to work safely in the laboratory as they progress through four years of undergraduate laboratory work. Most topics are covered several times, at increasing levels of depth, with progressively more advanced safety issues discussed